2020
DOI: 10.3389/fonc.2020.00720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between PET-CT–Guided Neck Dissection and Elective Neck Dissection in cT1-2N0 Tongue Squamous Cell Carcinoma

Abstract: Objective: Neck management in cT1-2N0 tongue squamous cell carcinoma (SCC) remains controversial. Our goal was to compare the survival difference between PET-CT-guided neck dissection and elective neck dissection (END) for the treatment of cT1-2 tongue SCC. Methods: Patients with surgically treated cT1-2N0 tongue SCC were retrospectively enrolled. These patients were divided into two groups. Group A: The decision of whether to perform neck dissection was mainly based on the results of preoperative PET-CT exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In this study we have provided evidence that multiple readers can achieve high NPV by visual assessment as well as by SUVmax analysis. This result has significant implications, especially managing the contralateral neck, as single center studies have now reported on the outcome of patients managed with observation of PET directed (negative) contralateral neck [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have provided evidence that multiple readers can achieve high NPV by visual assessment as well as by SUVmax analysis. This result has significant implications, especially managing the contralateral neck, as single center studies have now reported on the outcome of patients managed with observation of PET directed (negative) contralateral neck [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are limited by heterogeneous treatment, poorly described RT, and selection bias. Yet the reported contralateral neck failure rates in the absence of contralateral neck RT in these selected patients with pN0-2a surgical staging are reassuring, ranging from 0–12% [ 83 , 84 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. While no single risk factor appears to be independently and reliably associated with nodal recurrence, increasing the depth of invasion appears to confer the highest risk when combined with additional risk factors [ 83 ].…”
Section: Controversies In Patient Selection For Unilateral Neck Rt—oral Tongue Cancermentioning
confidence: 99%